Associated and digenean fauna of the mussel Mytilus galloprovincialis cultured on shellfish tables in the lagoon of Bizerta (Tunisia) ... - Gargouri Ben Abdallah, L.; Chargui, T.; Abidli, S.; Trigui El Menif, N. (University of Salento, 2012)
1 - Shellfish tables used for the breeding in bags of the oyster Crassostrea gigas and the mussel Mytilus galloprovincialis are suitable support for rapid colonization by marine living organisms.2 - During the period, June 2008 to May 2009, monthly samples of M. galloprovincialis were collected from the mytiliculture farm situated in Menzel Jemil (Bizerta Lagoon). Specimens were analyzed to identify their associated and digenean fauna.3 - Overall samples contain 68 taxa belonging to 12 zoological classes. Crustaceans, Polychaetes and Bivalves dominated largely the associated fauna, with frequencies of 34.7%, 22.9% and 10.6% respectively. The Polychaete Myrianida pinnigera was identified for the first time in the Tunisian coast. The remaining groups of associated fauna (Ascidia, Ophiuroids, Gastropods, Actinaria, Gymnolaemata, Demosponges, Calcispongia, Turbellaria, and Echinids,) accounted for only 31.8%. Diversity indices showed a temporal variation of the taxonomic structure of listed groups related to the ...